The genius as an anomaly in Diderot's aesthetic thought - Olszevicki, Nicolás Martín (Anales del Seminario de Historia de la Filosofía, 2025)
Diderot's concept of "genius” was never systematically elaborated in his writings. Nevertheless, it has been recognized as central in the transition from the aesthetics of Enlightenment to Romanticism. This paper aims to study this concept in its relationship with another central concept of Enlightenment aesthetics: "taste." We will propose that Diderot's thought entails a strong polemic with the doctrines defended by Condillac, Helvétius, and Voltaire. While for these authors, genius, reason, and taste were seen as natural allies in contributing to human progress (so that genius could be conceived as a supreme manifestation of the taste of the time), Diderot's exaltation of the monstrous character of genius implies an alternative, and revolutionary, way of conceiving its relationship with temporality, progress, and good taste.
Keywords: genius; taste; instant; Diderot